The Influence of the Index Card Match Model on Civics Learning Outcomes in Class IV Students at SD Inpres Kuanino 2, Kupang City - Leltakaeb, Aflegina; Nahak, Roswita L.; Nahak, Kristina E. Noya (Jurnal Ilmiah Mandala Education (JIME), 2024)
The Influence of the Index Card Match Model on Civics Learning Outcomes in Fourth Grade Students at SD Inpres Kuanino 2, Kupang City. Thesis of the Elementary School Teacher Education Study Program, Faculty of Education, Citra Bangsa University. Supervisor 1: Roswita Lioba Nahak, S. Pd., M. Pd., and Supervisor II: Kristina E Noya Nahak, S. Pd., M. Pd.The research aimed to determine the influence of the Index Card Match model on the learning outcomes of fourth-grade students at SD Inpres Kuanino 2, Kupang City. The study utilized a quasi-experimental design with a nonequivalent control group design type, involving a sample of 28 students. Data collection was done using multiple-choice test questions. Before hypothesis testing, the researcher conducted tests to meet the hypothesis requirements, including normality and homogeneity tests. The results showed that the data was normally distributed (0.121 > 0.05) and homogenous (0.188 > 0.05). The hypothesis testing used an independent sample t-test. The results of the independent sample t-test showed that the average score in the posttest for the control group was lower than the experimental group, with scores of 63.46 < 83.00 and a significance value of 0.000 < 0.05. This indicates a significant difference in the average scores between the control and experimental groups, leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Based on these findings, it can be concluded that the Index Card Match model has a significant influence on the learning outcomes of fourth-grade students.